Interstellar molecules their laboratory and interstellar habitat - Yamada, Koichi M. T.; Winnewisser, G. 1936- (Gisbert) (Springer tracts in modern physics, 2011)
This book deals with the astrophysics and spectroscopy of the interstellar molecules. In the introduction, overview and history of interstellar observations are described in order to help understanding how the modern astrophysics and molecular spectroscopy have been developed interactively. The recent progress in the study of this field, after the 4th Cologne-Bonn-Zermatt symposium 2003 is briefly summarized. Furthermore, the basic knowledge of molecular spectroscopy, which is essential to correctly comprehend the astrophysical observations, is presented in a compact form.